A fully integrated 4-channel beamformer based on TTD phased array in 0.18μm CMOS. (October 2018) - Liu, Youzhong; Zhang, Wei; Liu, Yanyan
Abstract: A fully integrated 4-channel beamformer based on TTD phased array is proposed in this paper. This architecture is especially suitable for MIMO systems which can increase throughput by improving multiplexing gain. A path-sharing true time delay (TTD) unit by using analog CMOS filter circuits is presented to realize flat time delay over 0.35–1 GHz. Compared to traditional MIMO architectures, highly multiplexed TTD reduces chip area and power consumption. The proposed beamformer can provide maximum scan angle of up to ±45°for four antennas with 10.5 cm spacing. The measurement results show that maximum delay is almost consistent with simulated results. Input signals from the same direction which reach different antennas, are delayed a different fixed time difference through different TTD units and have same phase at the output, realizing signal enhancement. The whole beamformer chip consumes 130 mA from a 1.8 V DC power supply, and has a total chip area of 4.65 mm × 4.30 mm.